Proceedings of the 8th International Conference on Learning Analytics and Knowledge 2018
DOI: 10.1145/3170358.3170369
|View full text |Cite
|
Sign up to set email alerts
|

Studying MOOC completion at scale using the MOOC replication framework

Abstract: Research on learner behaviors and course completion within Massive Open Online Courses (MOOCs) has been mostly confined to single courses, making the findings difficult to generalize across different data sets and to assess which contexts and types of courses these findings apply to. This paper reports on the development of the MOOC Replication Framework (MORF), a framework that facilitates the replication of previously published findings across multiple data sets and the seamless integration of new findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…[64]) or on replicating findings from one course in another (e.g. [3]), not on developing models that can be used across classes or class offerings. This is crucial because in order for a model to be useful it must be the case that we can train it before it is actually necessary.…”
Section: Introductionmentioning
confidence: 99%
“…[64]) or on replicating findings from one course in another (e.g. [3]), not on developing models that can be used across classes or class offerings. This is crucial because in order for a model to be useful it must be the case that we can train it before it is actually necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The limited MOOC replication research to date has shown that many published findings in the field may not replicate. For example, in a large-scale replication, [14] found that only 12 of 15 previously-published MOOC findings replicated significantly across the data sets, and that two findings replicated significantly in the opposite direction; similar results in a machine learning replication in the context of algorithm and feature selection were shown in [15].…”
Section: B Lack Of Replication Studies In Learning Sciencesmentioning
confidence: 68%
“…The open availability of executable machine learning experiments affords detailed meta-analyses by providing complete results of all modeling stages for meta-analysis. MORF has already been used for metaanalysis [14].…”
Section: B Beyond Verification: the Benefits Of Replicationmentioning
confidence: 99%
“…Other work has included information outside the clickstream, such as forum post data analyzed with natural language processing [10,17]. Frameworks for evaluating various models and their feature sets have also been introduced [15,22]. While most of these studies focused on only a small set of courses, [11,22] used a dataset of 20 or more courses to train and predict.…”
Section: Related Workmentioning
confidence: 99%
“…Frameworks for evaluating various models and their feature sets have also been introduced [15,22]. While most of these studies focused on only a small set of courses, [11,22] used a dataset of 20 or more courses to train and predict.…”
Section: Related Workmentioning
confidence: 99%